PENGARUH PANJANG STUM DAN KONSENTRASI PUPUK DAUN TERHADAP PERTUMBUHAN STUM MATA TIDUR TANAMAN KARET (Hevea brasiliensis Muell. Arg.) - Wahyu Nur Andika; Tri - Harwati; Hadi - Ariyantoro (Innofarm:Jurnal Inovasi Pertanian, 2013)
Research on "The Effect of Length stums and leaf fertilizer concentration on growth of stum rubber sleep eyes (Hevea brasiliensis Muell. Arg.). aimed to determine the effect of stum length and concentration leaf fertilizer concentration on growth of stum rubber sleep eyes, was carried on May 7, 2013 to August 2, 2013, in a plastic  house, garden experiments Slamet Riyadi Faculty of Agriculture, University of Surakarta, which is  located  in  the  village of  Mojosongo,  District  Banjarsari,  Surakarta  with altitude 143 meters above sea level. The method used in the research is arranged to use completely randomized design (CRD) with two treatment factors. The first factor cutting length 10 cm, 15 cm, and 20 cm. The second factor of Gandasil D leaf fertilizer 0 g/liter water, 1 g/liter water , 2 g/liter water, and 3g/liter water, in order to obtain 12 combinations of treatment and repeated 3 times. The results showed: (1) Stum length treatment effect on all the parameters are observed ie shoot height, number of leaves, bud diameter, amount of roots, bud fresh weight and dry weight of bud. Stum length 15 cm produces a good bud growth is 31.15 cm bud height and bud diameter 5.48 mm. Stum 20 cm long while the amount of leaves produced 11.84 strands, the amount of roots of pieces 7.40, 18.73 g shoot fresh weight, and bud dry weight of 3.66 g. (2) Concentration and leaf fertilizer Gandasil D height effect  on  all  parameters  was  observed  that  shoot  height,  number  of  leaves,  bud diameter, amount of roots, bud fresh weight and dry weight of bud. Concentration of 3 g / liter of water produces good growth is 31.39 cm tall bud, bud 6.18 mm diameter, the amount of leaves 12 pieces, the amount of pieces roots 7.55, 19.44 g bud fresh weight and  dry weight  of  bud  3  ,  80  g.(3) There is  no  interaction  treatment  length  and concentration of fertilizer stum Gandasil D observations on all parameters. Key words : Length stums, leaf fertilizer, stum rubber sleep eyes, Hevea brasiliensis